Growth models and the footprint of transnational capital - Patrick Kaczmarczyk (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2020)
The definition of various growth models is the latest innovation of comparative capitalism (CC) research. Yet, the literature has its weaknesses in explaining the dynamics within and the interdependencies between different growth models. I argue that this weakness stems inter alia from an inadequate conceptualization of transnational corporations (TNCs). I provide empirical evidence on the footprint of international capital in the global economy and outline how including TNCs as a unit of analysis can help us to better understand economic outcomes. This leads to several implications for the growth models literature, which I conclude my argument with.
Keywords: 330; institutions and the macroeconomy; international business; multinational firms; political economy